Neural control of sexually dimorphic behaviors. - Manoli, D.S.; Fan, P.; Fraser, E.J.; Shah, N.M. (Current Opinion in Neurobiology, 2013)
All sexually reproducing animals exhibit gender differences in behavior. Such sexual dimorphisms in behavior are most obvious in stereotyped displays that enhance reproductive success such as mating, aggression, and parental care. Sexually dimorphic behaviors are a consequence of a sexually differentiated nervous system, and recent studies in fruit flies and mice reveal novel insights into the neural mechanisms that control these behaviors. In the main, these include a diverse array of novel sex differences in the nervous system, surprisingly modular control of various stereotyped dimorphic behavioral routines, and unanticipated sensory and central modulation of mating. We start with a brief overview to provide the appropriate conceptual framework so that the advances made by the newer studies discussed subsequently can be fully appreciated. We restrict our review to reporting progress in understanding the basis of mating and aggression in fruit flies and mice.